The Effect of Combining Flap Fixation with Gentamicin Lavage of the Surgical Bed for Reducing Postmastectomy Seroma: A Single-Institute Experience - Mohamed Samir; Rabie Ramadan (Middle East Journal of Cancer, 2022)
Background: Seroma is the most prevalent complication after mastectomy and can lead to significant morbidity. No single method has been shown to be completely effective in reducing seroma rates. Flap fixation can reduce the dead space after mastectomy, thus decreasing the drainage volume and seroma rates. Gentamicin acts against Staphylococcus epidermidis involved in increasing drainage volume, duration, and seroma rates. This study aimed to evaluate the effect of combining flap fixation with gentamicin lavage of the surgical bed for reducing postmastectomy seroma. Method: This prospective randomized controlled study included 100 women with breast cancer scheduled for modified radical mastectomy (MRM). The patients were allocated into the following four groups of 25: GI: flap fixation; GII: surgical bed lavage with gentamicin-containing solution; GIII: both techniques used in GI and GII; GIV: control group. The patients were followed up for the registration of drainage volume, timing of drain removal, and incidence of seroma. Results: Total drainage volume was significantly lower; the drain was removed earlier and seroma rates were lower in group III than the other groups (P = 0.001, 0.009, and 0.005, respectively). Seroma in GIII was mild and managed with aspiration. In the other groups, seroma was more severe and required more aspirations, second tube drainage, or open drainage. Conclusion: Combining flap fixation and gentamicin lavage of the surgical bed after MRM significantly decreased the amount of drained fluid, allowing an earlier removal of the drain and decreasing the incidence of seroma when compared with using each procedure alone. Moreover, the severity of seroma was significantly lower when both techniques were combined.